On the impingement of heat transfer using swirled air jets - Kotb, Ashraf; Askar, Hamada; Saad, Hany (Frontiers in Mechanical Engineering, 2023)
An experimental analysis of the heat transfer between a constant heat flux flat plate and round air jet for both conventional as well as swirled jets. These experiments are carried out under the same experimental conditions. Vane-type swirl generators are used for producing a swirl. These swirl generators were inserted at the nozzle exit. The experimental measurements were performed at a fixed value of Reynolds number (Re =23000) calculated based on the jet tube inside diameter. A comparison between conventional air-jet and swirl jet with swirl numbers of S=0, 0.19, 0.42, and 0.72 are presented at the different nozzle to plate spacing, Z/D = 2, 6, and 10. The results showed that the heat transfer to the plate decreases when the nozzle to plate distance increases. Also increasing the swirl number S, increasing the heat transfer uniformity but decrease the global heat transfer. At low plate to jet distance Z/D =2 the point of maximum heat transfer is shifted to a radial position depending on the swirl number. Also, for both Z/D=6 and 10 the stagnation point, and stagnation region heat transfer enhancement only for swirl numbers of 0 and 0.19.